English Language Teaching Research in the Middle East and North Africa Multiple Perspectives - Hidri, Sahbi (Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
This book examines English Language Teaching (ELT) research in the Middle East and North Africa (MENA). While the MENA region has witnessed considerable change in recent years, it has so far tended to be under-represented in ELT research at both the regional and the international level. This book aims to help fill this gap by surveying the current state of the field, examining in detail a range of issues and concepts, and suggesting future directions for further research. The different parts cover topics as various as testing, evaluation and assessment; argumentation in discourse analysis; teaching diglossia in vocabulary; and the role of critical thinking in foreign language learning and teaching. It will be of interest to ELT researchers and practitioners internationally - not just those based in MENA contexts themselves. Sahbi Hidri is an assistant professor of applied linguistics at the Faculty of Human and Social Sciences of Tunis, Tunisia. He is the founder ofTunisia TESOL, the Arab Journal of Applied Linguistics and the Tunisian Association of Language Assessment and Evaluation.